The Size and Scope of Government in the US States: Does Party Ideology Matter? - Christian Bjørnskov; Niklas Potrafke (Center for Economic Studies and ifo Institute (CESifo), 2013)
We investigate empirically how party ideology influences size and scope of government as measured by the size of government, tax structure and labor market regulation. Our dataset comprises 49 US states over the 1993-2009 period. We employ the new data on the ideological mapping of US legislatures by Shor and McCarty (2011) that considers spatial and temporal differences in Democratic and Republican Party ideology. We distinguish between three types of divided government: overall divided government, proposal division and approval division. The main result suggests that Republican governors have been more active in deregulating labor markets. We find that ideology-induced policies were counteracted under overall divided government and proposal division.
Keywords: D72; 330; size of scope of government; party ideology; partisan politics; divided government